Thermoelectric microconverter for energy harvesting systems - Carmo, João Paulo Pereira (2010)
This paper presents a solution for energy microgeneration through energy harvesting by taking advantage of temperature differences that are converted into electrical energy using the Seebeck effect. A thermoelectric microconverter for energy scavenging systems that can supply low-power electronics was fabricated using thin films of bismuth and antimony tellurides. Thin films of n-type bismuth (Bi2Te3) and p-type antimony (Sb2Te3) tellurides were obtained by thermal coevaporation with thermoelectric figures of merit (ZT) at room temperature of 0.84 and 0.5 and power factors (PF × 10−3 [W · K−1 · m−2]) of 4.87 and 2.81, respectively. The films were patterned by photolithography and wet-etching techniques. The goal for this thermoelectric microconverter is to supply individual electroencephalogram (EEG) modules composed by an electrode, processing electronics, and an antenna, where the power consumption ranges from hundredths of microwatts to a few milliwatts. Moreover, these wireless EEG modules allow patients to maintain their mobility while simultaneously having their electrical brain activity monitored.